MORAL STATUS OF CORPORATIONS - Kodirov Tuygun Uzokovich (American Journals Publishing, 2023)
In the article Today's widely developed Corporation and its ethical situation, The history of the corporation, analysis of views on the moral state of corporations, information on corporate culture and its importance in business development.
Keywords: Corporation, ethics, spirituality, business, management, social, responsibility, reform, charity, state.